Experimental study of antiexudative action of «Venogel 911 with horse chestnut» - Komissarenko, Andrei; Avidzba, Yulia; Nikolov, Valentin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Regardless of the degree of injury, it is necessary to use conservative methods for the treatment of patients with injuries, in particular medications using local remedies. Among the drugs used to treat chronic venous insufficiency, directly affect the main mechanisms of the pathogenesis of venoactive (phlebitropic) agents. They protect the venous wall from the influence of local mediators, oxidants, stabilize the membranes of endotheliocytes, reduce the permeability of venules and capillaries, increase the tone of the veins and their elasticity, i.e. they have complex endothelioprotective and venoprotective action. Objective: to investigate the anti-exudative action of «Venogel 911 with horse chestnut» in the experiment. Methods: a study of the anti-exudative activity of gelabalzam «Venogel 911 with horse chestnut» in comparison with the reference preparations was carried out on the model of thermal inflammation of the mice foot. Results: the use of drugs resulted in marked suppression of swelling in the foot tissues of animals, which was exposed to a thermal stimulus, as evidenced by a statistically significant decrease in its mass. There were no significant differences in the anti-exudative activity «Venogel 911 with horse chestnut» in comparison with «Gingoven» and «Dr. Teisse Venen gel». <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> it has been established that «Venobal gel 911 with horse chestnut» has anti-inflammatory and anti-exudative action and can be used as a means for skin care of the legs, which is prone to manifestations of varicose insufficiency.